2023
DOI: 10.1186/s42826-023-00169-0
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus xylosus and Staphylococcus aureus as commensals and pathogens on murine skin

Abstract: Skin ulcers, skin dermatitis and skin infections are common phenomena in colonies of laboratory mice and are often found at increased prevalence in certain immunocompromised strains. While in many cases these skin conditions are mild, in other cases they can be severe and lead to animal morbidity. Furthermore, the presence of skin infections and ulcerations can complicate the interpretation of experimental protocols, including those examining immune cell activation. Bacterial species in the genus Staphylococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 127 publications
0
1
0
Order By: Relevance
“…And results found that Weissella cibaria had the greatest impact on health, followed by Staphylococcus xylosus and Leuconostoc pseudoteneteroides . Staphylococcus xylosus and Leuconostoc pseudomonas are opportunistic pathogens that can cause infection only in certain situations such as trauma, surgery, or immunosuppression ( 35 , 36 ). Weissella cibaria is a newly discovered Gram-positive bacterium belonging to the Lactobacillus family, widely present in various naturally fermented foods ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…And results found that Weissella cibaria had the greatest impact on health, followed by Staphylococcus xylosus and Leuconostoc pseudoteneteroides . Staphylococcus xylosus and Leuconostoc pseudomonas are opportunistic pathogens that can cause infection only in certain situations such as trauma, surgery, or immunosuppression ( 35 , 36 ). Weissella cibaria is a newly discovered Gram-positive bacterium belonging to the Lactobacillus family, widely present in various naturally fermented foods ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…aureus , S . xylosus has been shown to cause invasive disease in otherwise healthy carrier mice albeit that the mechanisms promoting colonization or infection have not been investigated [ 79 ]. We surmise that loss of S .…”
Section: Discussionmentioning
confidence: 99%
“…The level of staph bacteria recovered from IL17RA KO mice was also lower than that found in DKO mice (Figure 5B). Genomic sequencing showed that recovered bacteria were Staphylococcus xylosus (Supplementary Figure S8C), a staph species prominent on mouse skin (38)(39)(40) and a frequent cause of skin infections in mice (41)(42)(43)(44)(45).…”
Section: Dko Mice Have Increased Susceptibility To Staphylococcal Ski...mentioning
confidence: 99%